MANAJEMEN KEMITRAAN PROGRAM PINTAR BERSAMA DAIHATSU DI SMK NEGERI RAWAS ULU KABUPATEN MUSI RAWAS UTARA - Ratna, Parmi; Danim, Sudarwan (UNIVERSITAS BENGKULU, 2023)
The purpose of this research is to describe the fulfillment of minimum standards for educational facilities and infrastructure in public junior high schools. The method in this research is descriptive quantitative. Population in Muara Beliti sub-district, North Musi Rawas Regency. Data collection techniques are observation and documentation. Data analysis techniques use average formulas and percentages. The results of the study showed the fulfillment of elementary school facilities in the Muara Beliti sub-district, Musi Rawas Regency, was in the sufficient category, with details of the fulfillment of infrastructure standards in the good category and the fulfillment of facility standards in the sufficient category. Furthermore, it is suggested that the school principal make collaborative efforts with stakeholders and related National Education Offices in fulfilling school facilities.